Association between fertility treatments and breast cancer risk in women with a family history or BRCA mutations: a systematic review and meta-analysis - Liu, Xiaojing; Yue, Jing; Pervaiz, Ruqiya; Zhang, Hanwang; Wang, Lan (Frontiers in Endocrinology, 2022)
Objective: Women with hereditary breast cancer factors are more likely to be infertile and tend to receive fertility treatments. The safety of fertility treatments that contain hormone-related medications for ovarian stimulation has gained wide attention; however, evidence of the safety of fertility treatments is limited. This study aims to assess the association between fertility treatments and the incidence rate of breast cancer in women with a family history of breast cancer or BRCA1/2 mutations. Methods: A literature search was conducted in PubMed, Cochrane Library, and Embase. Studies concerning the effect of fertility treatments on breast cancer risk in genetically susceptible women were included. The fixed and random effects models were used to estimate the summary effects. Risk Of Bias In Non-randomized Studies - of Interventions instrument was used to assess the risk of bias in the included studies. Results: A total of 5,282 studies were screened. Five cohort studies and three case-control studies were included. Breast cancer risk was not significantly increased by fertility treatments in general genetically susceptible women (pooled odds ratio [OR] 1.18, 95% confidence interval [CI] 0.96–1.45), women with a family history of breast cancer (pooled OR 1.35, 95% CI 0.97–1.89), or women with BRCA mutations (pooled OR 1.02, 95% CI 0.74–1.4). In subgroup analyses, there was no significant increase in breast cancer risk whether in BRCA1 mutation carriers (pooled OR 1.18, 95% CI 0.81–1.72), BRCA2 mutation carriers (pooled OR 0.54, 95% CI 0.09–3.34), or in the women treated with IVF (pooled OR 0.75, 95% CI 0.51–1.1), CC (pooled OR 1.07, 95% CI 0.78–1.45) or gonadotropins (pooled OR 1.32, 95% CI 0.8–2.18). Discussion: This is the first meta-analysis concerning the impact of fertility treatments on breast cancer risk in genetically susceptible women. Despite the finding that fertility treatment did not significantly increase breast cancer risk in genetically susceptible women, large prospective cohorts with more detailed information are required. Further investigations are needed to explore the genetic background of hormone-related breast cancer and the association between BRCA1/2 mutations and the incidence of hormone receptor-positive breast cancer. Registration number: PROSPERO(CRD42021281336).